Characteristics, attitudes, and the odds for positive attitude toward clinical trial: A study on Indonesian COVID-19 vaccine trial participants - Nani Maharani; Nuvi Gustriawanto; Yetty M Nency; Endang Mahati; Glenn F Yeremia; Dimas T Anantyo; Rebriarina Hapsari; Mulyono Mulyono; Setyo G Pramudo; Nur Farhanah (Perspectives in Clinical Research, 2023)
Aims: This study was performed to understand the Indonesian population's characteristics and the factors that contribute to a more positive attitude toward participation in a clinical trial. Methods: A cross-sectional survey was conducted involving 402 COVID-19 vaccine trial participants in Semarang, Indonesia, utilizing self-reporting questionnaires consisting of questions related to socio-demographic characteristics and statements in a 5-scaled Likert Scale to assess the attitude toward vaccine trial. The odds for positive attitude were analyzed using Ordinal Logistic Regression to obtain the odd-ratio and 95% confidence interval. The P < 0.05 was considered statistically significant. Results: Most of the respondents were adults aged 22–64-year-old (89.30%), males (63.68%), married (77.61%), worked as an employee (59.70%), obtained information about the clinical trial from the Public Health Service (41.29%), had a low education level (40.80%), a low monthly income level (68.41%), with no previous participation in a clinical trial (90.80%). All respondents showed a good attitude toward the trial, with low education level, nonemployment status, fewer or no previous participation in clinical trials, and getting the information from the public health centers were the main predictors for better attitude toward vaccine trials. Conclusion: There was a positive attitude toward vaccine trials in the Indonesian population. The positive attitude could be driven by having a low education level, nonemployment status, fewer or no previous participation in the clinical trial, and getting information from public health centers.